Virtual Clinical Trials - Parker, Mark (Archives of Pharmacy, 2022)
Double Blind randomised controlled trials are the gold standard in estimating the clinical effect of medications, with pivotal phase 3 clinical trials forming the foundation a total revolution in healthcare decision making over recent decades. However, such trials are prohibitively expensive to conduct and the probability of a successful launch of a new medicine ranges from only 3% in nervous system disorders to 16% in anti-infectives . By considering Markov and Discrete Event Simulation models, now used extensively in post launch decision making globally, it is possible to conduct “virtual trials” at all launch phases to robustly analyse medications and their value as treatments.